Ultrastructural studies of the mandibular glands of the minima, media and soldier ants of Atta sexdens rubropilosa (Forel 1908) - Pavon, L. F.; Mathias, Maria Izabel Camargo [UNESP] (Elsevier B.V., 2005)
The mandibular glands of Hymenoptera are structures associated with the mandibles and constitute part of the salivary glands system. Histological studies in workers of Atta sexdens rubropilosa revealed that this gland contains two portions: a secretory and a storage portion or reservoir. Both portions are connected by means of canaliculi. The object of the present work was the study of the ultratructure of the mandibular glands of minima, media and soldier ant of A. s. rubropilosa by TEM techniques. The glands, in the three castes studied, possess a reservoir, constituted by a simple pavementous epithelium surrounded by the cuticular intima and the secretory portion is constituted by cells of rounded shape. The secretory cells, mainly of minima and soldier, were rich in smooth endoplasmic reticulum. The media worker and soldier presented a large number of mitochondria, of varying shape. Well-developed Golgi complexes were also present in the soldiers. The secretory cells in minima, media and soldier were provided with collecting intracellular canaliculi, which were linked to the reservoir through the extracellular portion. The cytoplasm of the canaliculi-forming cell was poor in organelles. In the individuals of the three castes of A. s. rubropilosa, the presence of lipid secretion granules suggested, beyond the other functions, also a possible pheromonal action. The different roles executed by the different insect castes are directly dependent on the glandular products and, consequently, on the secretory cellular characteristics. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: mandibular gland; Atta sexdens rubropilosa; ultrastructure; pheromone